Analysis of Habituation Learning in Mealworm Pupae (Tenebrio molitor) - Bernal-Gamboa, Rodolfo; García-Salazar, Jesús; Gámez, A. Matías (Frontiers in Psychology, 2021)
The decline of response as a consequence of repeated stimulation is known as habituation. The goal of the present experiments was extending the knowledge about habituation of abdominal contractions in the pupa of Tenebrio molitor. Both experiments consisted of two phases. During Phase 1, all groups were exposed to a continuous stimulus (light in Experiment 1 and vibration in Experiment 2). At the beginning of this phase, pupae showed a high number of abdominal contractions. However, during the last minute of Phase 1, the number of abdominal contractions was lower. In the next phase, the pupae were divided in different groups to test for response recovery. We found an increase in the abdominal contractions when subjects were exposed to a different stimulus, be it within the same or in a distinct sensory modality. In addition, we also reported response recovery when the pupae were re-exposed to the original stimuli after a resting period. Results indicate that the increase in responding cannot be explained by either sensory adaptation or fatigue. The findings are consistent with the perspective that suggests that habituation plays a major role in the survival of the species, even in non-feeding developmental stages.